Empathy and Sustainability: The Art of Thinking Like a Mountain: Workshop/Seminar 27-28-29 January 2023 Limassol, Cyprus - Kyprianidou, Efi; Christidis, Yiannis; Bantinaki, Katerina; Vasileiou, Fotini; Carpentier, Nico; Kouros, Theodoros (My University, 2023)
There is a growing realisation of the need for the 21st century culture sector and artistic creation to be able to both address the complex issues pertaining to climate change, the overexploitation of nature and the global health crisis and, at the same time, to enhance their own resilience. At the same time, the current covid-19 pandemic condition and the prolonged lockdowns enhanced the realisation that contemporary ways of living have undermined our sense of belonging to nature and emphasised the need to redefine the relation of human kind with other species of animal kingdom and nature. The seminar/workshop “The Art of Thinking Like a Mountain” highlighted the need of cooperation between philosophers, social scientists and artists, in order to raise awareness, to endow artists with the necessary knowledge and to find new ways to include sustainability and empathy in their disciplines.
Keywords: Empathy; Arts; Nature; Non-human beings